Bladder Neck Preservation During Radical Retropubic Prostatectomy and Postoperative Urinary Continence - Razi, Ali; Yahyazadeh, Seyed Reza; Sedighi Gilani, Mohammad Ali; Kazemeyni, Seyed Mohammad (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: Bladder neck-sparing modification of radical retropubic prostatectomy has been reported to lower the risk of urinary incontinence after prostatectomy. We reviewed the outcomes in men with prostate cancer who had undergone prostatectomy with either bladder neck preservation or bladder neck reconstruction. Materials and Methods:Â  In this retrospective study, a total of 103 patients who had undergone radical retropubic prostatectomy were assessed. The patients were divided into two groups of bladder neck preservation (51 patients) and bladder neck reconstruction (52 patients). We compared frequency of biochemical failure, bladder neck stricture, and urinary incontinence between these two groups. Biochemical failure was defined as a serum prostate-specific antigen level higher than 0.2 ng/mL and its rising trend in at least 2 postoperative subsequent measurements. Continence was defined as no need to use sanitary pads or diapers. Results: The two groups were comparable in terms of age, serum prostate-specific antigen level, Gleason score, and prostate volume. After a mean follow-up period of 32.5 months, all patients with bladder neck preservation and 46 (88.5%) with bladder neck reconstruction were continent (P = .03). There were no significant differences in the frequency of biochemical failure and bladder neck stricture that required dilation between the two groups of patients. Conclusion: Bladder neck preservation during radical retropubic prostatectomy may improve long-term results of urinary continence and be effective in eradicating prostate cancer without increasing recurrence rate.